Serving a New Nation : Baey Lian Peck's Singapore Story - Ooi, Kee Beng (Book collections on Project MUSE., 2011)
The story of Dr Baey Lian Peck should be well known, but it is not. Not even among Singaporeans, and especially not among the young. This tells us a lot about a Singapore caught in pathological haste and prone towards ignoring values that do not add to the financial bottom line. The innovativeness of Dr Baey did not only make him a very wealthy man before he was forty, it also made him an indispensable actor in the implementation of urgently constructed national policies. Political leaders such as Dr Toh Chin Chye, Lim Kim San, Chua Sian Chin and Dr Goh Keng Swee picked him to solve pressing pr.